Analisis Kebijakan Ujian Nasional (UN) terhadap Evaluasi Pendidikan - Muhammad Arrazi; Roni Saputra; Ridwal Trisoni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Evaluation is the act of assessing whether an educational program has achieved its goals, is effective, or has value. One evaluation tool used is the National Final Examination (Ujian Akhir Nasional or UAN), which has become a topic of debate. It should only be used for policy purposes, not for determining students' graduation, and is contradictory to education laws. The type of research used in this article is library research, referring to research that relies on existing references and literature. The article details issues in the education system, particularly concerning the National Final Examination, and the impact of new policies related to UAN in 2017. The National Examination has become a crucial element in Indonesia's education system with a unique history and development. Educational evaluation in the form of the National Examination helps measure progress and the quality of education nationally, with the goal of improving educational quality and meeting government-set standards..